Peran ecolabel awareness dan green perceived quality pada purchase intention - Dian Novita; Nurul Husna (Jurnal Manajemen Maranatha, 2020)
Global market recently tend to be concerning about green market with green product. The purpose of this paper is to analyze the impact of ecolabel awareness and green perceived quality on purchase intention. This research used probability sampling technique method with random sampling procedure but based on gender (female respondent), to represent all respondent that used green cosmetic product in Bandar Lampung. It was designed from three variabels using a Likert scale. It used SmartPLS 3.0 to analyze data. The finding of this study reveals that ecolabel awareness has positive but no significant direct effect on purchase intention, whereas green perceived quality has a positive and significant effect on purchase intention.